2016
DOI: 10.1002/da.22502
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Yoga for Reducing Depression and Anxiety, and Improving Well-Being: A Randomized Controlled Trial

Abstract: Yoga plus regular care was effective in reducing symptoms of depression compared with regular care alone. Further investigation is warranted regarding potential benefits in anxiety. Individualized yoga may be particularly beneficial in mental health care in the broader community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 83 publications
(166 reference statements)
2
91
1
7
Order By: Relevance
“…The FS (Diener et al, ) was used in two articles (Barrington & Shakespeare‐Finch, ; de Manincor et al, ). Both investigations were conducted in Australia using the eight‐item English version.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The FS (Diener et al, ) was used in two articles (Barrington & Shakespeare‐Finch, ; de Manincor et al, ). Both investigations were conducted in Australia using the eight‐item English version.…”
Section: Resultsmentioning
confidence: 99%
“…This study used the scale as a correlational variable. The second investigation (de Manincor et al, ) is a RCT aimed at testing the effect of an individualized yoga intervention versus waiting list in depressed and/or anxious patients. In this case, the scale was used as an outcome measure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the FS can now be used to assess efficacy of interventions aiming to increase well-being as a primary or secondary aim. Trials have shown that interventions such as a six-week yoga intervention (Manincor et al 2016), a web-based happiness training (Feicht et al 2013) and body-mind medicine (Gimpel et al 2014) can increase FS scores in different populations and settings. Second, there has been an increasing interest from governments to measure well-being at a national and international level in the past decade (Helliwell 2003).…”
Section: Discussionmentioning
confidence: 99%